Effects of metal fluoride/sulfide microparticles generated by consecutive high-pulse-power breakdowns on the insulating performance in compressed SF6. (8th October 2020) - Yan, Wenlong; Wang, Zhenxing; Shang, Wei; Su, Jiancang; Cao, Zhiyuan; Zhou, Zhipeng; Sun, Liqiong; Wang, Jianhua
Abstract: Spark gas switches (SGS) are widely used in various pulsed power applications where sulfur hexafluoride (SF6 ) is still dominant because of its excellent insulating performance. However, particle contamination generated by SF6 possesses some special properties that can greatly reduce the effectiveness of the gas switches. The objective of this paper is to study the effects of particles generated spontaneously by consecutive breakdowns of high-pulse-power SGS on the insulating performance in compressed SF6 . A double electrode/double pulse method, coupled with laser scattering and laser shadow photography, is adopted to detect the particles and examine their specific roles in the breakdown process. Many large particles in SF6, of approximately 150 μm in diameter, are observed at about 80 milliseconds after a single breakdown. Furthermore, numerous particles gradually suspend and accumulate in the gap after consecutive breakdowns. Particles generated by SF6 can reach tens of micrometers in size. They have rough microtopography covered by abundant floccules, and contain rich electronegative elements: fluorine and sulfur. Moreover, particle-involved abnormal breakdowns in SF6 usually occur with nearly equal threshold and probability in spite of the increasing consecutive breakdowns, and conversely, the abnormal breakdowns in N2 appear more frequently and unsteadily with a high dispersibility. The analysis of field enhancement caused by these large metal-fluoride/sulfide particles shows that they can directly cause significant field emission (FE) due to their properties of surface-field enhancement and causticity. Such FE further triggers micro-discharge. Subsequently, this behavior eventually leads to abnormal breakdowns at a lower threshold.